Hubungan Penggunaan Smartphone dengan Perilaku Makan pada Remaja di Kelurahan Oesapa - Hendrawan Litijawa; Yendris K. Syamruth; Marselinus Laga Nur (Yayasan Literasi Sains Indonesia, 2025)
Eating behavior in adolescents can be influenced by various factors, one of which is smartphone use. Adolescents, who are in a critical stage of development, are vulnerable to the negative impacts of excessive smartphone use, including changes in eating patterns. This study aims to analyze the relationship between smartphone use and eating behavior among adolescents in Oesapa Subdistrict. This is a descriptive analytic study with a cross-sectional design. The sample consisted of 86 adolescents aged 15–19 years. The sampling technique used was simple random sampling. Data were collected using a questionnaire consisting of two sections: questions regarding the duration of smartphone use and adolescent eating behavior. Data were analyzed using the chi-square test to examine the relationship between the two variables. The results showed that among the 86 respondents, smartphone use was categorized as high (87%), and eating behavior was categorized as good (85%). The chi-square analysis indicated that there was no significant relationship between smartphone use and eating behavior (p-value = 0.360) among adolescents in Oesapa Subdistrict. Adolescents are encouraged to reduce their level of smartphone use, maintain healthy eating habits, and engage in regular physical activity.